Cucurbitaceae Cultivation: Effects, Pest Management Alternatives, and Addressing Root-Knot Nematode - Varghese, Alan; Thomas, Preethi (Journal of Research in Science and Engineering, 2026)
This study explores the economic importance of the nematode dilemma in cucurbitaceae farming as well as the negative consequences of nematicides. Nematicides' pollution of the biosphere is investigated, and nematode control bio - pesticides are evaluated as potential substitutes. The research identifies practical countermeasures to nematicides' unfavourable effects. The symbiotic interaction between nematodes and cucurbit plants is shown by the research, highlighting its economic significance. Economic losses occur from the disruption of soil ecology, decreased fertility, and hampered agricultural production caused by excessive nematicide usage. It has been demonstrated that bio - pesticides are efficient, cost - efficient alternatives. Sustainable solutions are provided through integrated pest management and alternative control strategies. In order to guarantee long - term food security and environmental health, this study promotes sustainable agricultural practises.